Phases in the system Na1/2Nd1/2TiO 3-SrTiO3: A powder neutron diffraction study - Ranjan R.; Agrawal A.; Senyshyn A.; Boysen H. (My University, 2025)
A powder neutron diffraction study of (Na1/2Nd 1/2)1-xSrxTiO3 (NNST) has been carried out at room temperature. The system exhibits Pbnm space group for 0≤x≤0.20, Ibmm space group for 0.30≤x≤0.40, I4/mcm space group for 0.50≤x≤0.80 and space group for 0.90≤x≤1.00. The nature of these structural transitions is analysed in terms of the variation with composition of the lattice constants, octahedral tilting and strains. The results are discussed in the framework of group theoretical analysis of octahedral tilts in perovskites. © IOP Publishing Ltd.